2010
DOI: 10.1189/jlb.0210079
|View full text |Cite
|
Sign up to set email alerts
|

EphB2-mediated interactions are essential for proper migration of T cell progenitors during fetal thymus colonization

Abstract: The ephrin-Eph ligand receptor pair is known to control the repulsion/adhesion process in different tissues, including the immune system. Herein, we evaluated the role of EphB2 receptors in T cell progenitor migration during in vitro thymus colonization and to ECM or chemokine stimuli. EphB2 and their ligands, ephrin-B1 and ephrin-B2, are expressed in BM-derived progenitors, and EphB2(-/-) cells had diminished thymus colonization capacity. Conversely, EphB2(LacZ) cells, which maintain a preserved ephrin-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 57 publications
(81 reference statements)
9
49
0
Order By: Relevance
“…These results, therefore, confirm and extend previous data (13,14,36,37) that suggested both autonomous and nonautonomous effects of Eph/Ephrin-B in distinct aspects of thymus biology.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results, therefore, confirm and extend previous data (13,14,36,37) that suggested both autonomous and nonautonomous effects of Eph/Ephrin-B in distinct aspects of thymus biology.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, increased cell death observed in the DN cell subset and, in some mice, in DP and SP cells of the three studied mutants contribute to the decrease in thymic cellularity. In addition, we reported decreased lymphoid progenitor colonization of Eph B2 2/2 thymic stroma (37). Nevertheless, in thymocyte-conditioned ephrin-B1/-B2 mutants, there is also a significant increase in the proportions of proliferating cells, especially in the DP cell compartment, that could partially recover the cell content, a finding previously reported by others (40).…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, BM progenitors expressing a truncated form of EphB2 (EphB2-lacZ), that transmit reverse signals to the stromal cells of fetal thymic lobes, show normal migration. On the other hand, the relevance of TEC for controlling progenitor cell migration into the thymus is supported by the fact that migration of WT progenitor cells into EphB2-deficient thymic lobes (EphB2 -/-and EphB2-lacZ) is severely impaired [19] .…”
Section: Eph/ephrins and Guided Migration Of Thymocytesmentioning
confidence: 98%
“…We have demonstrated that EphB2-deficient bone marrow (BM) Lin-progenitor cells have a reduced capacity to colonize wild-type (WT) fetal thymic lobes in in vitro reconstitution assays, demonstrating an autonomous role for EphB2 in thymus-settling progenitors [19] . In contrast, BM progenitors expressing a truncated form of EphB2 (EphB2-lacZ), that transmit reverse signals to the stromal cells of fetal thymic lobes, show normal migration.…”
Section: Eph/ephrins and Guided Migration Of Thymocytesmentioning
confidence: 99%
“…Eph/ephrin interactions are implicated in mediating neuronal plasticity (reviewed by Yamaguchi and Pasquale, 2004;Dalva et al, 2007) and nerve re-growth after injury (Goldshmit et al, 2006;Liu et al, 2006;Du et al, 2007). In non-neuronal tissues, ephrins are required for such diverse processes as T-cell maturation and function (Stimamiglio et al, 2010), vascular growth and patterning (reviewed in Kuijper et al, 2007), bone homeostasis (reviewed by Edwards and Mundy, 2008), glucose metabolism and insulin secretion (Konstantinova et al, 2007;Kulkarni and Kahn, 2007). In the context of adult stem cells, ephrins mediate key activities in stem/progenitor cells of bone (Arthur et al, 2010), intestine (reviewed by Pitulescu and Adams, 2010), dental pulp (Stokowski et al, 2007) and hair follicles (Genander et al, 2010).…”
Section: Discussionmentioning
confidence: 99%